Association between bipolar disorder and subsequent traumatic brain injury in patients who received inpatient treatment. (March 2018) - Huang, Mei-Feng; Su, Chen-Hsiang; Tu, Hung-Pin; Liu, Tai-Ling; Lin, Chih-Lung; Chen, Cheng-Sheng; Yeh, Yi-Chun
Abstract: Mental disorders may confer a high risk of traumatic brain injury, but only rare studies have investigated mood disorders. This nationwide cohort study compared the risk of traumatic brain injury in patients with and without bipolar disorder. We compared 1017 patients with bipolar disorder who received inpatient treatment and 9080 compared patients. The annual incidence rate of traumatic brain injury was calculated as the number of new cases divided by the total number of person-years in the available records. The incidence of subsequent traumatic brain injury was significantly higher in the bipolar group than in control group. The adjusted hazard ratio for those with multiple hospitalizations was higher than the counterpart. Except for patients in the 50–59-year age group, those in all other age groups had higher risks of traumatic brain injury. Our findings reveal a higher risk of traumatic brain injury in patients with bipolar disorder. Patients with recurrent hospitalization and multiple psychotropic use had an increased risk of traumatic brain injury. Age may modify the risk of traumatic brain injury, with a higher risk in middle-aged patients. Highlights: Patients with bipolar disorder had a higher risk of traumatic brain injury The risk of traumatic brain injury was highest in the first 2 years after receiving the diagnosis if bipolar disorder. Age may modify the risk of traumatic brain injury, with a higher risk in middle-aged patients.